Foley music: an exploration of the relationships between sound design and 'music' in film - Mabitsela, Diale Daniel (My University, 2016)
Recently, scholarly work in the field of film sound design has emphasised the crucial significance of sound in film. Writers such as Mark Underwood (2008), Larry Sider (2003) and Danijela Kulezic-Wilson (2008) have expressed the view that film sound design ought to be approached from a musical perspective substantiating this position through analytical discussions on the relatively musical use of sound design in scenes from films such as Alfred Hitchcock’s The Birds (1963) and Darren Aronofsky’s Requiem for a Dream (2000). Building upon the work of these and other scholars, this thesis investigates the varying ways in which music and foley sound design relate and interact within a film seeking to categorise with some specificity the various ways in which foley sound design can ascend beyond its ordinary remit and in so doing function in lieu of film music as well as in cooperation with it. I consider examples from, amongst others, The Godfather, parts one (1972) and two (1974) by Francis Ford Coppola and The Matrix (1999) by Ana and Lana Wachowski. In each chapter of part one of the thesis (which I call Take 1), I explore a particular aspect of the way in which foley makes known its capacity to function quasi-musically. Chapter one looks at Walter Murch’s concept of the metaphoric use of sound and how, through this technique, foley sound can be applied so as to fulfil roles more accustomed to film music in its stead. Chapter two details some of the ways in which film music and foley interact within a film. A crucial element of this discussion is the on going debate between scholars such as Michel Chion who disavow the existence of a soundtrack and others such as Rick Altman who contradict Chion on this matter. Chapter three looks at how otherworldly diegetic contexts help to encourage creativity in designing and applying foley sounds so as to further enhance its pre-discussed ability to act in film music’s stead while chapter four focuses on the voice as the soloist within the melee of sounds that constitute the film soundtrack. Part two (or Take 2) of the thesis consists of compositions written in response to some of the theories and concepts explored in the first part of the thesis including a ‘dramatic string quartet’ in which I attempt to realise in a musical composition some of the ideas discussed in all four of the chapters. I conclude the thesis by reflecting on the main insights uncovered throughout the thesis in addition to reflecting on the process of composing the pieces in relation to the relative success of the performances thereof.
A thesis submitted to the Faculty of Humanities, University of the Witwatersrand, Johannesburg, in fulfilment of the requirements for the Degree of Master of Music Johannesburg 2016
Keywords: Motion picture music; Cinematography--Special effects; Sound--Recording and reproducing; Sound motion pictures; Music and technology